La verdadera cara del COVID-19 en Honduras: una lucha limitada por bajos recursos (Innovare: Revista de ciencia y tecnología, 2020)
Developing countries are undoubtedly confronting a major challenge with the COVID-19 outbreak, as their debilitated health care systems are facing the dichotomy of allocating resources on either semi-structured units of care or trying to amplify the already struck facilities. Moreover, many were already depleted of medical equipment prior to the outbreak. The rationale behind, was to describe the factors that conditioned an unfavorable environment to face the pandemic.On March 10th 2020, Honduras reported the first case of COVID 19. After 181 days, authorities confirmed 64,764 cases. The fatality rate at the beginning of the pandemic was alarmingly high fluctuating between 2% and as high as 17%. Moreover, frontline healthcare workers were among the first to die, reflecting a remarkably initial scarcity of personal protective equipment (Guan et al., 2019; SINAGER, s.f). Unsurprisingly, data surfacing amidst the outbreak is showing a variability in terms of fatality rates and severity factors across different regions. Large-scale testing has been identified as an effective strategy leading to early detection and consequently rapid isolation.